2019
DOI: 10.1002/ijc.32411
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC‐mediated DNA alterations: A possible new mechanism of carcinogenesis in EBV‐positive gastric cancer

Abstract: Mechanisms of viral oncogenesis are diverse and include the off‐target activity of enzymes expressed by the infected cells, which evolved to target viral genomes for controlling their infection. Among these enzymes, the single‐strand DNA editing capability of APOBECs represent a well‐conserved viral infection response that can also cause untoward mutations in the host DNA. Here we show, after evaluating somatic single‐nucleotide variations and transcriptome data in 240 gastric cancer samples, a positive correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 37 publications
5
26
0
Order By: Relevance
“…NPC reportedly contains APOBEC signature mutations that associate with A3A or A3B upregulation 7 . Additionally, in gastric and mammary tumors, EBV infection is associated with A3s expression and APOBEC signature mutation 8,9 . Consistently, we found that EBV‐LMP1 increased A3s expression, identifying a viral gene responsible for A3s upregulation (Figure 1).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…NPC reportedly contains APOBEC signature mutations that associate with A3A or A3B upregulation 7 . Additionally, in gastric and mammary tumors, EBV infection is associated with A3s expression and APOBEC signature mutation 8,9 . Consistently, we found that EBV‐LMP1 increased A3s expression, identifying a viral gene responsible for A3s upregulation (Figure 1).…”
Section: Discussionsupporting
confidence: 74%
“…7 Additionally, in gastric and mammary tumors, EBV infection is associated with A3s expression and APOBEC signature mutation. 8,9 Consistently, we found that EBV-LMP1 increased A3s expression, identifying a viral gene responsible for A3s upregulation (Figure 1). Nonetheless, our 3D-PCR analysis did not detect increased mutation of nuclear genes, TP53 and PIK3CA, by A3s or LMP1 either in vitro or in vivo (Figures 2A and 3B, and Figs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…qPCR EBV-analysis (N = 400) showed 12.7% EBV+ in GC-cases and 2.9% in controls. We recently showed a possible new mechanism of EBV-carcinogenesis where EBV-infection triggers APOBEC3 over-expression and an APOBECmutation signature [7]. ii) Whole exome sequencing (WES) and RNA-Seq:…”
Section: Basic and Translational Gc Researchmentioning
confidence: 99%
“…Previous studies [4] have extracted distinct mutational signatures by examining a large set of human cancer genomes and some of these have been reported in the COSMIC database (denoted hereafter as CS). This pan-cancer analysis revealed significant heterogeneity of operational mutational processes, that encompass mutation-triggering events as diverse as the off-target activity AID/APOBEC family of cytidine deaminases, the exposure to ultraviolet light, tobacco-smoking and the defective DNA mismatch repair [5, 6].…”
Section: Introductionmentioning
confidence: 99%